Beginning Jakarta EE web development : using JSP, JSF, MySQL, and Apache Tomcat for building Java web applications - Manelli, Luciano (Apress, 2020)
Start building Java-based web applications now, even if youre a complete newcomer to Java. Comprehensive and example-driven, this book is all you need to develop dynamic Java-based web applications using JSP, connect to databases with JSF, and put them into action using the popular open source Java web server, Apache Tomcat. Beginning Jakarta EE Web Development is a comprehensive introduction to building Java-based web applications using JSP, JSF, MySQL, and the Apache Tomcat web application server. Other APIs including JSON, JSTL, and XML parser are covered along the way. Key concepts are made easy to grasp with numerous working examples and a walk-through of the development of a complete ecommerce project. This book is written for professionals by practicing Java web application professionals and experts. You will: Build Java-based web applications using JSP and JSF with Eclipse Jakarta EE Configure your database with MySQL Define XML documents for your applications Use the Apache MyFaces APIs to create JSF applications Integrate and implement JSF and JSP together Build an online ecommerce web application.